PERANCANGAN PALLET DELIVERY UNTUK MEMINIMASI RISIKO KELUHAN AKIBAT KERJA MENGGUNAKAN METODE RAPID ENTIRE BODY ASSESSMENT (REBA) DI PT. XYZ - Imdam, Irma Agustiningsih; Kurnianto, Radif; Sukmawati, Wilda; Sumasto, Fredy; Pratama, Indra Rizki; Marizka, Dewi Auditiya (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
Pallet Delivery Design at PT. XYZ is intended to overcome operator working posture problems in the manual process of tying boxes with ropes, so as to reduce complaints of Musculoskeletal Disorders (MSDs) in operators. Analysis of MSDs complaints was carried out by distributing the Nordic Body Map (NBM) questionnaire to three workers with the results that they experienced complaints of calf, back and knee pain. Based on the results of the Nordic Body Map questionnaire, a Rapid Entire Body Assessment (REBA) analysis was carried out, namely to assess the level of risk. In the initial assessment, REBA produced a score of 9 which indicates a high risk with the use of the tool used. To find out the specifications of the tool to be designed, it is done by measuring the operator's anthropometric data, followed by product design using the Need, Idea, Decision, and Action (NIDA) method as a design approach and the next stage is simulated in CATIA software to confirm risk reduction. The design simulation shows a decrease in the REBA value from 9 to 2, thereby reducing the risk of MSDs for workers.